Impact of Umbilical Cord Milking on Hematological Parameters in Preterm Neonates With Placental Insufficiency - Nagy, Mohammed; Nasef, Nehad; Gibreel, Ahmed; Sarhan, Mohamed; Aldomiaty, Hoda; Darwish, Mohammed; Nour, Islam (Frontiers in Pediatrics, 2022)
Background: Data is still lacking about the expediency of umbilical cord milking (UCM) in preterm neonates born to mothers with placental insufficiency (PI). Objective: To study the effect of UCM in preterm neonates who had ante-natal evidence of placental insufficiency on peripheral blood cluster of differentiation (CD34) percentage, hematological indices, and clinical outcomes. Methods: Preterm neonates, < 34 weeks’ gestation, born to mothers with evidence of placental insufficiency underwent UCM (PI+UCM group) were compared with historical controls whose umbilical stumps were immediately clamped (PI+ICC (immediate cord clamping) group) in a case-control study. Peripheral blood CD34 percentage as a measure of hematopoietic stem cells transfusion was the primary outcome. Early and late-onset anemia; polycythemia; frequency of PRBCs (packed Red blood cells) transfusion during NICU stay; peak total serum bilirubin (TSB); incidence of phototherapy, admission rectal temperature; first 24 hours’ hypothermia and hypoglycemia; episodes of hypotension and need for volume expander boluses and inotropic support during the first 24 h of age; duration of oxygen therapy; bronchopulmonary dysplasia (BPD); severe intra-ventricular haemorrhage (IVH); necrotizing enterocolitis (NEC); culture-proven late-onset sepsis; length of hospital stay; and in-hospital mortality were secondary outcomes. Results: In preterm infants with placental insufficiency umbilical cord milking was associated with greater peripheral blood CD34 percentage, hemoglobin levels initially and at postnatal age of 2 months, alongside significantly shorter duration of oxygen therapy compared with ICC group. Frequency of packed RBCs transfusion during hospital stay was comparable. Neonates in UCM group had a greater peak TSB level during admission with significantly higher need for phototherapy initiation compared with ICC. Logistic regression, adjusted for gestational age, revealed that UCM resulted in greater CD34 percentage, higher initial hemoglobin level, higher peak serum bilirubin, significant increase of phototherapy initiation, and higher hemoglobin level at 2 months. Conclusions: UCM in preterm neonates born to mothers with placental insufficiency was feasible and resulted in greater CD34 percentage, higher initial hemoglobin level, higher peak serum bilirubin, significant increase of phototherapy initiation, and higher hemoglobin level at 2 months.